Assessment of ototoxicity of intratympanic administration of Auralgan in a chinchilla animal model. (4th December 2014) - Mujica‐Mota, Mario A.; Bezdjian, Aren; Salehi, Pezhman; Schermbrucker, Jonah; Daniel, Sam J.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Auralgan (benzocaine and antipyrine) is an over‐the‐counter otic drug commonly used for otalgia. Nevertheless, there is limited evidence about the effects of the drug on hearing function and cochlear morphology in the presence of a tympanic membrane perforation. The aim of the present study was to assess the cytotoxicity of Auralgan using cultured auditory cells (HEI‐OC1) and to examine its effects on hearing function and cochlear morphology after intratympanic administration in a chinchilla model. Study Design Animal experiment. Methods Cell viability and DNA labeling assays were conducted to investigate the cytotoxic effect of the drug on cultured auditory cells (HEI‐OC1). To examine the possible drug ototoxic effect in vivo, chinchillas received intratympanic injection of Auralgan in one ear, whereas the contralateral control ear received saline. Outcome measures included auditory brainstem response and postmortem cochlear morphology. Results A dose‐dependent toxic effect of Auralgan was noted on cultured cells. Animal experiments showed an inflammatory reaction in the experimental ears and facial paralysis in 80% of the animals on the side receiving transtympanic injection of Auralgan (P < .05). Auditory brainstem response testing demonstrated a 30‐ to 50‐dB hearing threshold shift across all frequencies tested (P < .05). Control ears showed no inflammation or significant threshold shift. Microscopy showed damage to the hair cells and stria vascularis with bleeding in the perilymphatic space in the experimental ears and damage to the hair cells. Conclusions Auralgan was cytotoxic to cultured auditory cells. It promoted an inflammatory reaction and seemed to be ototoxic when given via transtympanic injection in an animal model. Level of Evidence NA Laryngoscope, 125:1444–1448, 2015